The Development of a model of instructional management by using education Satellite long distance (DLTV) in a small schools under the Office of Petchaburi Primary Education Service Area 2 - Sisanga, Manit; Chotientip, Tassanee; Maneephruek , Wirat (Journal for Developing the Social and Community, 2022)
The objectives of this research were to study the condition of teaching and learning management by using remote education via satellite (DLTV) in small schools and to develop a model for teaching and learning management by using remote education via satellite (DLTV) for small schools Under the Phetchaburi Primary Educational Service Area Office 2, the research method was Mixed Methods Research, both quantitative. and qualitative There are 6 steps of research procedures and methods, namely 1) the study of documents, concepts and theories related to teaching and learning management; using distance education via satellite (DLTV) by analyzing and synthesizing the content of principles, concepts and theories related to distance education via satellite (DLTV) and teaching management using satellite distance education ( DLTV) to determine the issue of the condition of teaching management by using remote education via satellite (DLTV) for small schools 2) to study the condition of teaching and learning management by using remote education via satellite (DLTV) in small schools by studying 2 types, namely quantitative, by asking for opinions from the target population. who are academic teachers of 75 people and school administrators of 75 people in small schools that provide teaching by using remote education via satellite (DLTV) of 122 schools and qualitatively By conducting in-depth interviews with the target groups who are teachers and small school administrators, the mainstay of teaching and learning by using satellite distance education (DLTV) in small schools. Under the Phetchaburi Primary Educational Service Area Office 2, everyone in Wat Huai Suea School (Mongkhon Prachasan) 3) Creating a model for teaching and learning by using satellite distance education (DLTV) in small schools. By studying the principles, concepts and research related to satellite distance education (DLTV) in small schools. and teaching management by using remote education via satellite (DLTV) in small schools In addition, the results of the study of teaching and learning management by using remote education via satellite (DLTV) in small schools. synthesize a draft teaching management model Presenting an expert review and scrutiny Coverage and approval of the draft model 4) Examination of the suitability and feasibility of the draft model for teaching and learning management using distance education via satellite (DLTV) in small schools. by discussing specific issues (Focus Group Discussion) of 10 experts, considering the appropriateness and feasibility of the model. 5) Improve and present teaching and learning management by using distance education via satellite (DLTV). in a small school by improving and presenting a model of teaching and learning management using distance education via satellite (DLTV) in small schools as recommended by experts. 6) Ask for opinions on the learning management model. Teach using satellite distance education (DLTV) in small schools. by asking for the opinions of the stakeholders and stakeholders From the target group who are school administrators, academic teachers in small schools that organize teaching by using remote education via satellite (DLTV) in every small school. and study the supervisors responsible for all schools in all network centers, amounting to 50 people, using a questionnaire for opinions on the model in terms of usefulness possibility side suitability and accuracy The result of study revealed that 1. The condition of teaching and learning management by using remote education via satellite (DLTV) in small schools Overall and in each aspect, the practice was at a high level. 2. Teaching management model using distance education via satellite (DLTV) in small schools Under the Office of Phetchaburi Primary Educational Service Area 2, the model of operation was 8 components, 84 indicators, namely planning, 10 indicators, development of related personnel, 10 indicators, teaching management, 12 indicators. Indicates roles and duties of stakeholders, number 10, participation, 10, support, 10, evaluation, 10, and networking, 10 indicators